PRESTASI KERJA KARYAWAN : PENGARUH KERJASAMA KELOMPOK, DISIPLIN DAN MOTIVASI KERJA (STUDI KASUS PADA PT. SINAR SOSRO KP. BENGKULU) - Sintia Safrianti (Universitas Prof. Dr. Hazairin SH, 2020)
The aim of the study is to know determine the effect of group cooperation, discipline and workmotivation on employee performance at PT. Sinar Sosro kp. Bengkulu. The variables examinedin this study were group cooperation, discipline and work motivation. Methods of data analysisusing instrument tests, classical assumption tests, and statistical tests. The data collectiontechniques and tools in this study were in the form of field data and library data. The sample inthis study were 35 employees of PT. Sinar Sosro kp. Bengkulu. The results of the study, bothgroup cooperation, discipline and work motivation variables have an effect on workperformance either partially or simultaneously